Genomic alterations in cholangiocarcinoma: clinical significance and relevance to therapy - Marianeve Carotenuto; Alessandra Sacco; Laura Forgione; Nicola Normanno (Open Exploration Publishing Inc., 2022)
Improving the survival of patients with cholangiocarcinoma (CCA) has long proved challenging, although the treatment of this disease nowadays is on advancement. The historical invariability of survival outcomes and the limited number of agents known to be effective in the treatment of this disease has increased the number of studies designed to identify genetic targetable hits that can be efficacious for novel therapies. In this respect, the increasing feasibility of molecular profiling starting either from tumor tissue or circulating cell-free DNA (cfDNA) has led to an increased understanding of CCA biology. Intrahepatic CCA (iCCA) and extrahepatic CCA (eCCA) display different and typical patterns of actionable genomic alterations, which offer opportunity for therapeutic intervention. This review article will summarize the current knowledge on the genomic alterations of iCCA and eCCA, provide information on the main technologies for genomic profiling using either tumor tissue or cfDNA, and briefly discuss the main clinical trials with targeted agents in this disease.